Utilization of visual inspection with acetic-acid in cervical cancer screening among health workers in secondary health care institutions of Kaduna state, Nigeria - Balarabe, Fatima; Musa, Umar; Chado, Mohammed Alfa; Ladan, Muhammad Awwal; Abdul, Halima Musa; Khalid, Dalhat Sani (Medknow Publications, 2015)
Aims: The research was conducted to investigate the utilization of visual inspection with acetic-acid (VIA) in cervical cancer screening among health workers in secondary health care institutions of Kaduna-state. Settings and Design: An Ex-post facto design was used for the study. The study population comprises all nurses, midwives, and nurse-midwives working in all the secondary healthcare institutions of Kaduna-state. The sample size used for the study was 300 using the Yamane, (1967) sample size selection formula. Subjects and Methods: The technique involved were stratified sampling method whereby the three existing senatorial zones served as strata. Each of the stratums was clustered according to the existing local government areas. A purposive sampling was further used to select nine local governments, three from each senatorial zone that have secondary health care institutions. A proportionate sampling was used at the various selected secondary health care institutions to distribute the questionnaire to the health workers based on their total number. The instruments used for data collection were the four-point level likert scale questionnaire, which was structured. 300 questionnaire copies were administered out of which (297) were retrieved. Statistical Analysis Used: The data collected were analyzed using one-way analysis of variance and two sample t-test at 0.05 level of confidence to answer the hypothesis. Significant difference exist in the demographic variables of age-group, sex, professional category, years of working experience and secondary health care institutions) in the utilization of VIA among health workers in secondary health care institutions of Kaduna-state (P < 0.05). A post-hoc Scheffe test was further used to determine where the differences were. Results: However, the overall results reveals that health workers in secondary healthcare institutions of Kaduna-state are not utilizing VIA in cervical cancer screening with an aggregate mean score of (2.1625) and (P < 0.05). Conclusions: It was concluded that health workers in secondary health care institutions of Kaduna-state are not utilizing VIA to screen for cervical cancer. It is therefore recommended that specialist VIA units should be created in the hospitals specifically for VIA screening services; this will go a long way in utilizing VIA to screen for cervical cancer by the health workers thereby reducing the high incidence of the disease.